The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0482-50042007000100007
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos clínicos e terapêuticos da osteomielite vertebral por fungos: análise secundária de dados

Abstract: Objectives: to assess the bibliometric, clinical and therapeutic features of fungal vertebral osteomyelitis case reports, retrieved from electronic databases. Methods: systematic review with secondary data analysis done on proven cases from Medline, Embase and Lilacs databases and active search of referenced published reports, since 1966 until 2004. Results: there was a growing trend from 1966 to 2004 (R 2 = 0.5518) in the 318 retrieved cases of fungal vertebral osteomyelitis: 218/318 (68.5%) of them from 1990… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(13 reference statements)
0
2
0
2
Order By: Relevance
“…13,23 Besides intramedullary spinal cord involvement, intradural extramedullary granulomas may occur, as well as epidural bone lesions involving the spinous process, the lamina and the vertebral bodies, causing osteomyelitis and spondylodiscitis. [24][25][26][27][28] There is evidence that the concomitant use of corticosteroids with antifungal therapy can reduce the inflammatory process in patients with PCM. 2 The drugs most used in the antifungal treatment are itraconazole, sulfamethoxazole/trimethoprim, and amphotericin B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,23 Besides intramedullary spinal cord involvement, intradural extramedullary granulomas may occur, as well as epidural bone lesions involving the spinous process, the lamina and the vertebral bodies, causing osteomyelitis and spondylodiscitis. [24][25][26][27][28] There is evidence that the concomitant use of corticosteroids with antifungal therapy can reduce the inflammatory process in patients with PCM. 2 The drugs most used in the antifungal treatment are itraconazole, sulfamethoxazole/trimethoprim, and amphotericin B.…”
Section: Discussionmentioning
confidence: 99%
“…13 23 Besides intramedullary spinal cord involvement, intradural extramedullary granulomas may occur, as well as epidural bone lesions involving the spinous process, the lamina and the vertebral bodies, causing osteomyelitis and spondylodiscitis. 24 25 26 27 28…”
Section: Discussionmentioning
confidence: 99%
“…Espec ally the ncrease n the poss b l t es n the f eld of rad ology prov des fac l tates d agnos s. Although there s a l m ted number of b bl ometr c analyzes for spec f c VO publ cat ons n the ava lable l terature [24][25][26][27] , no study provd ng an overv ew was found. In th s study, we a med to g ve a v s on to those who w ll work on VO w th the b blometr c analys s method over the Scopus database.…”
Section: Discussionmentioning
confidence: 99%
“…Uma vez dentro do osso, as bactérias proliferam e desencadeiam uma resposta inflamatória, resultando em destruição do tecido ósseo (LEW & WALDVOGEL, 2004;HEITZMANN et al, 2019). Outras causas menos comuns podem incluir infecções fúngicas ou parasitárias (FIGUEIREDO et al, 2007).…”
Section: Introductionunclassified